2001
DOI: 10.1515/hf.2001.086
|View full text |Cite
|
Sign up to set email alerts
|

Directional Characteristics of Near Infrared Light Reflected from Wood

Abstract: A near infrared auto-goniophotometer was designed to acquire detailed information on optical characteristics of a biological material which had a cellular structure, such as wood. The reflected light, which originated from the irradiation of polarized near infrared light, was separated into an unpolarized and a polarized component by using two polarizing filters. The standardized reflected intensities of each component at various incident angles q and observation angles h, r up (q, h) and r p (q, h), were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This model, however, is not directly applicable to solid wood surfaces in the tangential direction because smooth surfaces scatter less IR radiation (Tsuchikawa and Tsutsumi 1999;Tsuchikawa et al 2001). We assumed that (1) linear correlation of this minimum with total lignin can be adapted to spectra collected from solid wood and (2) surface spectra represent the total lignin content of a sample after a given incubation time.…”
Section: Prediction Of the Lignin Content Of Decayed Wood Samplesmentioning
confidence: 99%
“…This model, however, is not directly applicable to solid wood surfaces in the tangential direction because smooth surfaces scatter less IR radiation (Tsuchikawa and Tsutsumi 1999;Tsuchikawa et al 2001). We assumed that (1) linear correlation of this minimum with total lignin can be adapted to spectra collected from solid wood and (2) surface spectra represent the total lignin content of a sample after a given incubation time.…”
Section: Prediction Of the Lignin Content Of Decayed Wood Samplesmentioning
confidence: 99%
“…The best prediction occurred for the aspen CIE b* colour space parameter (R 2 = 0.68; Figure 3), and the CIE L* colour space parameter (R 2 = 0.43) obtained in the range 400-900 nm confirmed that surface inactivation due to high temperature exposure induces veneer coloration changes (Gaintantzopoulou et al 2009). These changes are attributed to chemistry changes related to the disruption of hydrogen bonding and structural damage produced by the heat treatment (Tsuchikawa et al 2001, Meder et al 2002. Koumbi-Mounanga et al (2013) also found a good prediction of the CIE L* colour space parameter (R 2 = 0.54) using 400-900 nm spectral data for Douglas-fir (Pseudotsuga menziesii var.…”
Section: Discussionmentioning
confidence: 86%
“…First, it has a limited penetration depth in solid wood, from 1 mm to 5 mm depending on surface roughness and the wavelength used (Tsuchikawa et al 1996, 2001, Sykes et al 2005. More penetrating radiations, such as microwaves should be tested for estimating bulk MC of boards.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to test a more deterministic approach that uses optical models like the one of the Tsuchikawa et al (2001). Also, in this study, we derived board MC images from NIR-HSI.…”
Section: Discussionmentioning
confidence: 99%